A 49-year-old Women with Pain and Blurring of Vision in Right Eye - Nobi, Md Ayakub; Reza, Ishrat Binte; Hossain, Farhana; HAM Nazmul Ahasan (Journal of Medicine, 2025)
Orbital pseudotumor is a rare benign non-infective inflammatory condition of the orbit without any identifiable local or systemic causes. It has various clinical manifestations. The clinical diagnosis is based on the exclusion of orbital neoplasm, infections, and orbital manifestation of systemic illness. We report the case of a 49-year-old female presented to Popular Medical College and Hospital with the complain of progressive deteriorating symptoms of her right eye, including pain, swelling, blurring of vision, and headache without having any history of trauma or recent infection or flare up of any systemic illness. Examination of eye showed erythema, peri-orbital oedema, drooping of upper eye lid with restricted eye movement in right eye. Magnetic resonance imaging revealed orbital soft tissue enhancement. A diagnosis of orbital pseudotumor was made on the basis of inflammatory markers and Magnetic Resonance Imaging findings. She was treated with oral corticosteroids. J MEDICINE 2025; 26: 74-76